2013
DOI: 10.1504/ijcrc.2013.056924
|View full text |Cite
|
Sign up to set email alerts
|

Digital creativity in dementia care support

Abstract: This paper reports the application of digital creativity to the care for people with dementia. A digital app was developed for use by staff in residential homes caring for people with dementia. The app invokes a set of computational services to undertake creative work, the results of which are presented to encourage and support cognitive creativity by care staff. The services undertake computational work such as retrieving resolutions to care problems encountered previously, matching care situations to situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Because of their importance to cognition, analogies have interested researchers in the field of artificial intelligence. Systems for the computation of analogies have been created since the '60s for many different purposes such as solving puzzles based on objects in images [3], obtaining information by inference [9], understanding the development in analogical reasoning in children [16], or even as support in suggesting specialized care for patients with dementia [21]. Recent contributions in natural language processing [14] have suggested that analogical inference can be directly performed as vector operations on word vectors (e.g., Paris ≈ France + Berlin − Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their importance to cognition, analogies have interested researchers in the field of artificial intelligence. Systems for the computation of analogies have been created since the '60s for many different purposes such as solving puzzles based on objects in images [3], obtaining information by inference [9], understanding the development in analogical reasoning in children [16], or even as support in suggesting specialized care for patients with dementia [21]. Recent contributions in natural language processing [14] have suggested that analogical inference can be directly performed as vector operations on word vectors (e.g., Paris ≈ France + Berlin − Germany).…”
Section: Introductionmentioning
confidence: 99%
“…No entender de Pitts et al (2015) constatouse que nas avaliações feitas pelos técnicos houve uma 'reflection-in-action' em detrimento de uma 'reflection-on-action'. Neste contexto, Zachos et al (2013) propõem a utilização de uma App designada por «Carer» com o objetivo de estar ao serviço dos técnicos/cuidadores de forma a utilizar a tecnologia de uma forma criativa. Ou seja, a App contem um conjunto de hipotéticos cenários associados a comportamentos de doentes com demências e que desafiam os técnicos de saúde/cuidadores a criarem, a reformularem, a acrescentarem, a adaptarem e a complementarem novos cená-rios que registam na App e que passam a estar disponibilizados por toda a comunidade de técnicos de saúde/cuidadores.…”
unclassified